2017
DOI: 10.1038/s41598-017-02251-9
|View full text |Cite
|
Sign up to set email alerts
|

Weak stromal Caveolin-1 expression in colorectal liver metastases predicts poor prognosis after hepatectomy for liver-only colorectal metastases

Abstract: Loss of stromal Caveolin-1 (CAV1) expression is associated with poor prognosis in various cancers. We evaluated the prognostic value of CAV1 expression of both cancer cells and stromal cells in colorectal liver metastases (CRLM) in patients undergoing hepatectomy. In this retrospective study, 109 patients were enrolled. CAV1 expression was studied by immunohistochemistry. The staining was scored semiquantitatively as weak or strong. Disease-free survival (DFS) and overall survival (OS) were calculated using bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
(75 reference statements)
0
14
0
Order By: Relevance
“…Liver -CAV1 expression was increased in HCC compared to normal liver and correlated with tumorigenesis and metastasis; metastasis could be linked to upregulated Wnt/b-catenin pathway; 191 increased cell motility and migration 192,193 -CAV1 expression in HCC inhibited autophagy and was linked to decreased overall survival 146 -Decreased overall survival in patients with weak CAV1 expression in stromal cells of colorectal liver metastases 194 Bladder -CAV1 was overexpressed in 1/3 of patients undergoing radical cystectomy and could be associated with decreased overall survival 195 -Expression contributed to migration and induced EMT through a PI3K/Akt dependent pathway 196 Gastric cancer -High expression of CAV1 in advanced tumors, whereas early staged tumors showed low levels of CAV1; associated with opposite RAF-ERK signaling, cell cycle progression and colony forming ability 197 -Patients with CAV1-positive tumors after gastrectomy displayed a decreased disease-free and overall survival; 198 CAV1-expression was associated with poor prognosis in gastric cancer 199 -Low CAV1 expression in gastric cancer patients in comparison to healthy stomach tissue; gastric cancer cell lines of primary tumors displayed low levels of CAV1, whereas cell lines originated from metastases show high expression levels 200 -CAV1-deficient or low expressing CAFs are associated with a decreased overalls and disease-free survival; CAV1-status of CAFs could be used as a prognostic marker 123,201 Cervical cancer -CAV1 expression in tumor cells may contribute to cell proliferation and was associated with positive HPV-infection 202 -Upregulation of CAV1 and MTCH2 was induced by DHA treatment in HeLa cells and leads to enhanced p53 dependent cell death 203 may be a critical step for tumor progression. 69,73 A multivariate analysis of CAV1 immuno-reactivity in adenocarcinoma specimens further suggested that CAV1 is an independent functional predictor of poor survival.…”
Section: -Stromal Bone Marrow Cells Induce Cav1 Expression In Cll Celmentioning
confidence: 99%
“…Liver -CAV1 expression was increased in HCC compared to normal liver and correlated with tumorigenesis and metastasis; metastasis could be linked to upregulated Wnt/b-catenin pathway; 191 increased cell motility and migration 192,193 -CAV1 expression in HCC inhibited autophagy and was linked to decreased overall survival 146 -Decreased overall survival in patients with weak CAV1 expression in stromal cells of colorectal liver metastases 194 Bladder -CAV1 was overexpressed in 1/3 of patients undergoing radical cystectomy and could be associated with decreased overall survival 195 -Expression contributed to migration and induced EMT through a PI3K/Akt dependent pathway 196 Gastric cancer -High expression of CAV1 in advanced tumors, whereas early staged tumors showed low levels of CAV1; associated with opposite RAF-ERK signaling, cell cycle progression and colony forming ability 197 -Patients with CAV1-positive tumors after gastrectomy displayed a decreased disease-free and overall survival; 198 CAV1-expression was associated with poor prognosis in gastric cancer 199 -Low CAV1 expression in gastric cancer patients in comparison to healthy stomach tissue; gastric cancer cell lines of primary tumors displayed low levels of CAV1, whereas cell lines originated from metastases show high expression levels 200 -CAV1-deficient or low expressing CAFs are associated with a decreased overalls and disease-free survival; CAV1-status of CAFs could be used as a prognostic marker 123,201 Cervical cancer -CAV1 expression in tumor cells may contribute to cell proliferation and was associated with positive HPV-infection 202 -Upregulation of CAV1 and MTCH2 was induced by DHA treatment in HeLa cells and leads to enhanced p53 dependent cell death 203 may be a critical step for tumor progression. 69,73 A multivariate analysis of CAV1 immuno-reactivity in adenocarcinoma specimens further suggested that CAV1 is an independent functional predictor of poor survival.…”
Section: -Stromal Bone Marrow Cells Induce Cav1 Expression In Cll Celmentioning
confidence: 99%
“…Decreased expression of Caveolin-1 has been identified as a main cause of how malignant cells are provided with nutrients [153155]. One study was found to investigate the role of CAV-1 in survival after resection of CRLM [156]. This study demonstrated decreased stromal CAV1 staining intensity to be a significant biomarker for decreased overall survival by multivariate analysis.…”
Section: Resultsmentioning
confidence: 90%
“…Two studies analysed survival in relation to both tumour and stroma caveolin‐1 expression 54,64 . Six studies related tumour cell caveolin‐1 expression (1365 patients) with DFS 54,60,62,64,67 and in seven studies (998 patients) stroma expression was related with DFS 48,49,52,54,56,64 . Three studies were not eligible for survival analysis 44,46,68 …”
Section: Resultsmentioning
confidence: 99%